2009
DOI: 10.1262/jrd.20145
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Cyclic Change of Betaglycan in the Rat Oviduct

Abstract: Abstract. Although the fallopian tube provides a sufficient environment for fertilization and early embryo development, the mechanism by which it does this is unclear. It is known that the transforming growth factorβ (TGFβ) superfamily plays important roles in various reproductive functions. Betaglycan, originally characterized as a TGFβ type III receptor lacking a clearly identifiable signaling motif, has been shown to be important for the high-affinity binding of TGFβs to the type II receptor. To our knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Expression of TGFβ‐superfamily ligands and their receptors has been reported in the oviduct of a variety of species (Dalton et al, ; Zhao et al, ; Chow et al, ; Kubota et al, ; Jiwakanon et al, ), and is often dependent on the oestrous cycle and pregnancy, suggesting that ovarian steroids contribute to their regulation (Zhao et al, ). We found that Tgfb1 level decreased in the myosalpinx at 1 and 3 hr post‐mating while abundance of TGFBR3 protein increased 3 hr earlier in the myosalpinx of mated versus unmated rats, although this did not correlate with Tgfbr3 transcript levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of TGFβ‐superfamily ligands and their receptors has been reported in the oviduct of a variety of species (Dalton et al, ; Zhao et al, ; Chow et al, ; Kubota et al, ; Jiwakanon et al, ), and is often dependent on the oestrous cycle and pregnancy, suggesting that ovarian steroids contribute to their regulation (Zhao et al, ). We found that Tgfb1 level decreased in the myosalpinx at 1 and 3 hr post‐mating while abundance of TGFBR3 protein increased 3 hr earlier in the myosalpinx of mated versus unmated rats, although this did not correlate with Tgfbr3 transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…Upon deposition of semen, seminal TGFb1 modulates the immune response by interacting with epithelial cells of the female reproductive tract (Robertson et al, 2002). Expression of TGFb1 and its receptors have been reported in rat, mouse, and human oviducts; in all cases, the TGFb1 secreted into the oviduct and uterine fluid influences the sperm, oocyte, spermÀoocyte interactions, and early-embryo development (Zhao et al, 1994;Chow et al, 2001;Jones et al, 2006;Kubota et al, 2009;Omwandho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%